Photocatalytic mineralization of benzene over gold containing titania nanotubes: role of adsorbed water and nanosize gold crystallites - Awate, S. V.; Sahu, R. K.; Kadgaonkar, Mahesh D.; Kumar, R.; Gupta, N. M. (Catalysis Today, 2009)
Well aligned titania nanotubes, with surface area of similar to 150 m(2) g(-1) and average pore diameter of similar to 5 nm, have been synthesized by subjecting a mesoporous TiO(2) sample to alkaline treatment followed by calcination at different temperatures. Composite catalysts with gold particles dispersed in these nanotubes were also synthesized and their structural, morphological, optical and photocatalytic properties were examined. The catalytic activity of TiO(2) for UV-mediated photo-oxidation of benzene was found to be affected by several factors, such as the sample texture. presence of adsorbed water and gold crystallites. The overall conversion of benzene to form CO(2) followed a trend: Au/nanotube > TiO(2) nanotubes > mesoporous TiO(2). In situ IR spectroscopy revealed that the adsorption and reaction of benzene molecules gave rise to formation of certain phenolic species over TiO(2), while the temperature-programmed desorption (TPD) study showed that the Au/TiO(2) interfaces serve as distinct sites for the adsorption and activation of oxygen molecules. It is suggested that certain hydroxyl and oxygen ion radicals produced under UV-irradiation may promote the deep oxidation of surface phenolic species and phenoxyl (ArO center dot) type transient radicals. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Benzene degradation; Gold containing; Photocatalyst; Role of adsorbed water; TiO(2) nanotubes; Transient species

Photocatalytic degradation of methylene blue on Sn-doped titania nanoparticles synthesized by solution combustion route - Bhange, P. D.; Awate, S. V.; Gholap, Ramkrishna S.; Gokavi, G. S.; Bhange, Deu S. (Materials Research Bulletin, 2016)
Series of tin-doped titania nanoparticles with varying tin content in the range 0-20 mol% have been prepared by solution combustion synthesis route using urea as a fuel. The structure, surface morphology and optical activity of Sn-doped TiO2 nanoparticles were investigated by various analytical techniques such as powder XRD, SEM, TEM, UV-vis and N-2 adsorption study. The crystalline structures of the various phases were studied by rietveld refinement of the XRD data. The photocatalytic performance of Sn-doped titania nanoparticles were tested for degradation of MB under UV and visible light irradiation. The results reveal that the photocatalytic activity increases with increase in tin content which may be due to decrease in crystallite size with increase in surface area. The doping of Sn into TiO2 lattice hinders the recombination of electrons and holes thus enhance the quantum efficiency of photocatalytic reaction. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; composites; Nanostructures; X-ray diffraction